Structure-function analysis of the human papillomavirus type 16 E7 oncoprotein. - Phelps, W C (1992)
The E7 gene of human papillomavirus type 16 encodes a multifunctional nuclear phosphoprotein that is functionally and structurally similar to the adenovirus (Ad) E1A proteins and the T antigens of other papovaviruses. E7 can cooperate with an activated ras oncogene to transform primary rodent cells, trans activate the Ad E2 promoter, and abrogate transforming growth factor beta-mediated repression of c-myc. Recent studies suggest that these functions may in part be a consequence of the ability of E7 to associate with the product of the retinoblastoma tumor suppressor gene (pRB). In this study, a series of site-specific mutations of the human papillomavirus type 16 E7 gene product were constructed and assessed for their effects on intracellular protein stability, ras cooperativity, transcriptional trans activation, pRB association, and phosphorylation. The results of these studies indicate that the transforming and trans-activating domains extensively overlap within a region of the protein analogous to conserved region 2 of Ad E1A, suggesting that pRB binding is necessary for both activities. Deletion of sequences in conserved region 1 abrogates cellular transformation but has only a marginal effect on trans activation. These data suggest that E7 trans activation and cellular transformation are interrelated but separable functions.